A Need Analysis on Media in Teaching English to Young Learners: Exploring Appropriateness and Advantages - Sushy Teko Patanduk; Rachel; Normalia Sirande; Tidar Julian (Universitas Cokroaminoto Palopo, 2023)
This paper presents a need analysis on the use of media in teaching English to young learners especially in doing community service on teaching English to children on early ages in Toraja. The aim of the study was to assess the specific media preferences and advantages associated with incorporating media in language instruction for young learners. Through a systematic investigation, the study aimed to inform educators and curriculum developers about the appropriate media used in the English language classroom and the advantages in implementing the medias. Based on result of data analysis, it can be concluded that picture storybook, animation video, interactive games, song, and things around are very important to be used when teaching English to young learners. Regarding to the advantages, it found out that media can be beneficial to be implemented in teaching English for several reason. They are: enhancing learners' motivation, facilitating different learning style, fun and enjoyable learning experience, fostering learners' understanding, and also fostering effective and interactive learning.